2018
DOI: 10.1101/356295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ras inhibition by trametinib treatment in Drosophila attenuates gut pathology in females and extends lifespan in both sexes

Abstract: Females of most species live longer than do males. Furthermore, lifespan-extending interventions in laboratory model organisms are often more effective in females (Regan and Partridge 2013). For instance, genetic and pharmacological suppression of activity of the insulin/insulin-like signalling -target of rapamycin (IIS-TOR) network generally extends female lifespan more than that of males in both Drosophila and mice (Clancy et al. 2001;Selman et al. 2009). We previously showed that attenuation of Ras-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The Drosophila gut is a major immune locus, responding to infection by producing AMPs and reactive oxygen species (122,123). Infection-induced immune responses are observable in males (122); however, while a small number of studies have compared sex differences in gut metabolism (124), and physiology (24,(124)(125)(126), most work on intestinal immunity has focussed on females. Nothing is known about sex dimorphisms in AMP or ROS production, nor indeed survival, after oral infection.…”
Section: The Intestinal Epitheliummentioning
confidence: 99%
“…The Drosophila gut is a major immune locus, responding to infection by producing AMPs and reactive oxygen species (122,123). Infection-induced immune responses are observable in males (122); however, while a small number of studies have compared sex differences in gut metabolism (124), and physiology (24,(124)(125)(126), most work on intestinal immunity has focussed on females. Nothing is known about sex dimorphisms in AMP or ROS production, nor indeed survival, after oral infection.…”
Section: The Intestinal Epitheliummentioning
confidence: 99%
“…This effect has been demonstrated in multiple ways in females through manipulation of diet 63 or the microbiome 38 and through genetic targeting of junctional components 64 or upstream signaling pathways 30,65 . Males do not usually respond strongly to manipulations that attenuate functional decline of the intestine 17,62 , including rapamycin 28 (this study), probably because progression of intestinal pathology is slow. Here, we showed that males were also sensitive to barrier function decline by genetically targeting autophagy components, which increased the incidence of barrier function failure and decreased lifespan.…”
Section: Articlementioning
confidence: 76%
“…https://doi.org/10.1038/s43587-022-00308-7 tissue aging and responses to geroprotective drugs. Drosophila females treated with rapamycin show a strong lifespan extension in response to treatment with rapamycin 28 , and the fly offers a tractable system for understanding dimorphisms in tissue ageing 17 and responses to anti-aging therapeutics 20,62 . Treatment of Drosophila with rapamycin extended lifespan in females, but not in males, regardless of their genetic background.…”
Section: Articlementioning
confidence: 99%
“…This has been demonstrated in multiple ways in females through manipulation of diet 59 , the microbiome 38 , and through genetic targeting of junctional components 60 or upstream signalling pathways 29,61 . Males do not usually respond strongly to manipulations that attenuate functional decline of the intestine 16,58 , including rapamycin ( 27 and this study), likely because progression of intestinal pathology is slow. Here, we show that males are also sensitive to barrier function decline, by genetically targeting autophagy components, which increased the incidence of barrier function failure, and decreased lifespan in males.…”
Section: Discussionmentioning
confidence: 87%
“…In one study, female mice were found to have higher circulating levels of rapamycin than did males for a given dose in the food 24 , suggesting that sex differences in drug metabolism or bioavailability could play a role in dimorphic responses to pharmaceutical therapies 12 . Drosophila, which shows a strong lifespan extension in females treated with rapamycin 27 , offers a tractable system for understanding tissue-specific contributions to ageing dimorphisms 16 , and dimorphic responses to anti-ageing therapeutics 19,58 .…”
Section: Discussionmentioning
confidence: 99%